68 Incidence of Secondary Intervention for Peyronie's Disease after Collagenase Clostridium Histolyticum. Issue 1 (1st April 2022) - Nackeeran, S; Masterson, T
ABSTRACT: Introduction: Collagenase clostridium histolyticum (CCH) is the only FDA-approved medical therapy for Peyronie's Disease (PD). It is unknown how many men will elect for surgical correction after CCH treatment. Other surgical options exist, including penile plication, incision and grafting and penile prosthesis. By studying patients within the Veterans Health Administration (VHA), who are all insured and therefore not limited by cost, we aimed to determine the percentage of patients electing additional surgical correction after treatment with CCH. Objective: To determine the need for secondary surgical correction after CCH Methods: We queried the VA Informatics and Computing Infrastructure (VINCI), the VHA's national database, to identify veterans with a diagnosis of PD by ICD-9 or ICD-10 code between 2015-2020. We searched medication codes for CCH and surgical CPT codes to determine which patients had the following procedures PD: plaque injection (CPT 54200), penile prosthesis (54400, 54405), penile reconstruction to correct penis angle (54360), or plaque excision (54110, 54111, 54112). Patients with medication codes for CCH and another procedure were assumed to have had surgery after CCH. Results: In total, 17, 647 veterans were diagnosed with PD. Of those, 1295 (7.3%) were treated with CCH. Of those who were treated with CCH, 100 (7.7%) elected for intervention after CCH. Within the group 61 had penile prosthesis, 23 had penile plication, and 32 had plaque excision and grafting (16 combined with IPP). Conclusions: Approximately 7% veterans who are treated with CCH injection elect secondary surgical correction. This indicates that CCH is an efficacious option for men suffering from PD, and a particularly beneficial choice for those who do not want surgery. Disclosure: No